Potential for large‐bodied zooplankton and dreissenids to alter the productivity and autotrophic structure of lakes. Issue 8 (1st August 2014) - Higgins, Scott N.; Althouse, B.; Devlin, S. P.; Vadeboncoeur, Y.; Vander Zanden, M. J.
Abstract : While limnological studies have emphasized the importance of grazers on algal biomass and primary production in pelagic habitats, few studies have examined their potential role in altering total ecosystem primary production and it's partitioning between pelagic and benthic habitats. We modified an existing ecosystem production model to include biotic feedbacks associated with two groups of large‐bodied grazers of phytoplankton (large‐bodied zooplankton and dreissenid mussels) and estimated their effects on total ecosystem production (TEP), and the partitioning of TEP between phytoplankton and periphyton (autotrophic structure) across large gradients in lake size and total phosphorus (TP) concentration. Model results indicated that these filter feeders were capable of reducing whole‐lake phytoplankton production by 20–70%, and increasing whole‐lake benthic production between 0% and 600%. Grazer effects on TEP were constrained by lake size, trophic status, and potential feedbacks between grazing and maximum rates of benthic photosynthesis (BPMAX ). In small (mean depth Z¯ < 10 m) oligotrophic and mesotrophic (TP < 100 mg P/m 2 ) lakes, both large‐bodied zooplankton and dreissenids were capable of increasing the benthic fraction (Bf) by 10–50% of TEP. Small lakes were also the only systems where TEP had the potential to increase in the presence of large‐bodied grazers, but such increases only occurred if grazer‐induced changes in water clarity, macrophyte coverage, or nutrient availability stimulated specific growth rates of periphyton. In other scenarios, TEP declined by a maximum of 50%. In very large lakes ( Z¯ > 100 m), Bf was minor (<10%) in the presence or absence of grazers, but increases in littoral habitat and the stimulation of benthic production in these ecosystems could be of ecological relevance because littoral zones in large lakes contain a relatively high proportion of within‐lake biodiversity and are important for whole‐lake food webs.